PENDAMPINGAN IMPLEMENTASI PEMIKIRAN MODERAT MUHAMMAD QURAISH SHIHAB DALAM TAFSIR AL MISHBAH PADA KAJIAN TAFSIR WALI MURID DI TK MUSLIMAT II, BEKASI - Badru Tamam; Lalu Muhiba; Abd. Muid Nawawi; Ahmad Husnul Hakim; Saiful Hidayat (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2023)
Moderation is fair and balanced thinking to avoid extreme behavior in its implementation. The principles that are important to understand and practice in moderation are justice, balance, and tolerance. People who always think moderately, have an open perspective on every difference, are gentle, calm in preaching, always provide convenience to others, eliminate difficulties, are not excessively fanatical so as to harm others towards one thought or group, and understand religious teachings comprehensively. Muhammad Quraish Shihab's thinking cannot be separated from the influence of his teacher at Al-Azhar Egypt, namely Sheikh Abdul Halim Mahmud, who is his exemplary teacher. His progressive views on life and diversity as well as a simple lifestyle also color the attitudes and views of Muhammad Quraish Shihab. The research methodology used is a qualitative method and is a library research by describing the views, understanding and interpretation of Muhammad Quraish Shihab regarding the basis of religious moderation obtained directly from his work, namely Tafsir al-Mishbah, with the theoretical framework of maudhu'i interpretation. The strategy is by collecting data through primary references, namely the book of Tafsir al-Mishbah which is the main reference. The second strategy is to process data using descriptive analytical method